Compare the Effect of Zinc–Probiotic versus Zinc Therapy in Acute Watery Diarrhea in Children (KYAMC Journal, 2023)
Background: Acute watery diarrhea still remains a major health problem among under 5 children worldwide. Apart from oral rehydration solution, continued feeding and oral zinc therapy the administration of adequate amounts of probiotics seems beneficial for acute diarrheal episodes in children in the developing world. Objective: To compare the efficacy of zinc-probiotic combination therapy versus zinc-only therapy in children with acute watery diarrhea. Materials and Methods: This was a hospital based randomized controlled clinical trial (RCT) conducted from July 2019 to June 2021 in the Department of Pediatrics, Khwaja Yunus Ali Medical College & Hospital. Total 70 children aged 6 months to 5 years admitted in hospital with acute watery diarrhea (AWD) with severe dehydration or some dehydration with intractable vomiting were included in this study. Patients were equally divided into 2 groups. Group A received oral zinc sulfate 20 mg/day for 10 days combined with oral Bacillus clausii probiotic 4million spores/day for 5 days. Group B received only oral zinc sulfate at the same dosage as group A. We also studied the relationship between mother`s education, knowledge of ORS preparation and child’s feeding practices and nutritional status with the occurrence of diarrhea in children. Results: Frequency of diarrhoea was significantly higher in group B (Zinc only) in comparison to group A (Zinc and probiotic). Mean frequency of diarrhea, Mean duration of diarrhea and Mean length of hospital stay was significantly higher in group B (Zinc) than group A (Zinc+Probiotic). Conclusion: Compared to oral Zinc therapy only; the combination of oral zinc and probiotic therapy is clinically more effective in reducing the frequency of acute watery diarrhea in under 5 years children.KYAMC Journal Vol. 13, No. 04, January 2023: 218-222